2020
DOI: 10.3390/app10030776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Landing Posture on Jump Height Calculated from Flight Time

Abstract: Flight time is widely used to calculate jump height because of its simple and inexpensive application. However, this method is known to give different results than the calculation from vertical velocity at takeoff. The purpose of this study is to quantify the effect of postural changes between takeoff and landing on the jump height from flight time. Twenty-seven participants performed three vertical jumps with arm swing. Three-dimensional coordinates of anatomical landmarks and the ground reaction force were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Aside from the 1FP method demonstrating criterion validity when predicting actual DH and touchdown velocity, there was also no fixed or proportional bias for any of the DJ performance variables reported (Tables 1 and 2). The comparable jump heights between methods were estimated from take-off velocity which is positive as it eliminates the error associated with flight time-estimated jump height due to differences in take-off and landing posture [24]. This is why the accuracy of the 1FP method for determining DH [5,10] which involves predicting propulsion net impulse from flight-time estimated jump height and then subtracting this from the entire net impulse to predict braking net impulse (and then using braking net impulse to predict DH), can be questionable [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the 1FP method demonstrating criterion validity when predicting actual DH and touchdown velocity, there was also no fixed or proportional bias for any of the DJ performance variables reported (Tables 1 and 2). The comparable jump heights between methods were estimated from take-off velocity which is positive as it eliminates the error associated with flight time-estimated jump height due to differences in take-off and landing posture [24]. This is why the accuracy of the 1FP method for determining DH [5,10] which involves predicting propulsion net impulse from flight-time estimated jump height and then subtracting this from the entire net impulse to predict braking net impulse (and then using braking net impulse to predict DH), can be questionable [7,8].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the dependent variables of forward dynamics procedures (e.g., velocity and power values) are affected to a greater extent by an inaccurate determination of the body weight during the bilateral CMJ [20]. By contrast, other variables that do not depend on the calculation of body weight, such as mean and peak force, were obtained with higher reliability during the bilateral CMJ [40,41]. These findings are partially in line with Bishop et al [19] who found a higher reliability (CV ratio = 1.29-1.63) for the bilateral CMJ compared to the unilateral CMJ in single-leg strength performance (mean force and concentric impulse).…”
Section: Plos Onementioning
confidence: 99%
“…For accelerometers, the inclusion of a gyroscope may account for landing position and trunk inclination [ 11 ], while linear transducers are advised to be set-up as vertical as possible. On the other hand, camera-based apps and micro-lasers use flight time primarily to calculate jump height, and therefore rely on proper jump and landing mechanics for accuracy [ 12 ]. The main difficulty with body-mounted accelerometers and camera-based applications is the correct identification of take-off and landing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%